Choosing Friends to Help a Victim of Domestic Violence in Surabaya - Sabri, Fahruddin Ali (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2023)
State actors and non-State actors have an important role and contribution to solving acts of domestic violence.  These actors are given space through Law No. 23 of 2004 concerning the Elimination of Domestic Violence. Legal protection and human rights are the main points for victims of domestic violence in protecting their dignity and dignity as human beings. Victims of domestic violence have the option to resolve it through both State and non-State actors, they seem comfortable with their choice of friends in resolving these acts of domestic violence. This article uses ethnographic methodology by observing the behavior, knowledge, beliefs, network of friends, and culture of the selection process for solving domestic violence in the city of Surabaya. This article is derived from data collected through documentation, semi-participant observation, and interactive dialogue. Friends as an institution where to complain, and seek resolution has been chosen by victims of domestic violence. They consider that friends play an important role as a preliminary institution rather than other actors such as nuclear relatives, police and courts who are State and other non-State actors.